Locus of Control Patterns in Headaches and Chronic Pain - Francisco Javier Cano-García; Luis Rodríguez-Franco; Ana María López-Jiménez (Pain Research and Management)
BACKGROUND: Locus of control (LOC) is related to the impact of headaches and chronic pain; however, literature evidence regarding LOC is not always consistent. Several authors consider this to be due, in part, to the separate interpretation of LOC factors, during which the interaction among them is ignored. In 1982, Wallston and Wallston proposed eight possible LOC health patterns depending on whether the individual scored high or low in each of three dimensions.